Collaboration with Industry in Designing Information Storage and Management Course - Kanakaraddi, Suvarna G.; Raikar, Meenaxi; Chikaraddi, A. K.; Jayalaxmi, G.; Shantala, G. (Journal of Engineering Education Transformations, 2018)
We live in a digital era deluged with huge data. An enormous amount of digital data is continually generated, collected, stored, and analyzed through software in the digital universe.The Industry- Institute interaction (III) is essential to innovate, inspire and envision the growth in the student’s career in the digital transformation era. The goal of III is to bring together the practitioners at industry, professors and students to collaborate in forming a community that encourages innovation in order to visualize enhanced user experience. To provide solutions on various domains most of the organizations are providing storage solutions. Among these organizations DELL-EMC is one of the leading storage solution providers. Information Storage and Management (ISM) course is introduced in the undergraduate curriculum by collaborating with DELL-EMC. EMC’s Curriculum on ISM course addresses the knowledge about storage technology emerging solutions. EMC Academic Alliance provides an opportunity to the students on ISM certification with free of cost. Based on these opportunities, ISM course contents are taken from EMC and course learning objectives are set according to the expectations of the industry. Authors have motivated the students by conducting online mock test on ISM certification. Through which students have got an exposure on writing certification exam. Certification exam on ISM is conducted and 50% of the students have qualified the exam with the target score of 85% at the semester end. This online certification creates an opportunity to the students to look for software jobs. Through this course we have mapped Department Program Outcome on Data Engineering criteria. With this course students have enhanced their skills in attempting online certification exams, which helps to build their career. By establishing the industry Alliance with DELL-EMC the authors are able to enhance the skills of students/next generation IT professionals on cloud technology, big data analytics and data storage.